MODERN APPROACHES TO THE TREATMENT OF HOMOZYGOUS FAMILIAL HYPERCHOLESTEROLEMIA - I. V. Leontyeva (Rossijskij Vestnik Perinatologii i Pediatrii, 2017)
Familial hypercholesterolemia remains a little-known disease in pediatric clinical practice, leading to late diagnosis and late initiation of therapy for this prognostically extremely unfavorable disease. The article presents modern ideas about etiology, genetic aspects. The diagnostic criteria and modern approaches to treatment are presented. The main clinical manifestations of the disease are cutaneous and tendon xanthomas, arcus lipoides of the cornea, generalized atherosclerosis of the coronary, brachiocephalic and femoral arteries. The consequence of these changes is the occurrence already in childhood of coronary heart disease and myocardial infarction. Effective lipid-lowering therapy was demonstrated in a child with homozygous hypercholesterolemia (2 mutations in the compound homozygous state in the LDLR gene). At the first stage, the child received combined therapy with statins (rosuvastatin in combination with ezetrol). The connection of the third drug, a type 9 inhibitor of proproteinconvertase, reduced the level of low-density lipoprotein cholesterol by another 15%, which was accompanied by regression of xanthomas. No adverse effects of therapy were observed.